Adolescent Transitions in Self-Management Strategies and Young Adult Alcohol Use. Issue 1 (March 2021) - Griffin, Kenneth W.; Scheier, Lawrence M.; Komarc, Martin; Botvin, Gilbert J.
Individuals use a variety of strategies to manage their thoughts, emotions, and behaviors across the lifespan. In this study, we used latent class analysis to derive distinct subtypes of self-management skills in early adolescence and latent transition analysis to examine whether movement between different classes was associated with later young adult alcohol use. Assessments of behavioral self-control, affective self-regulation, and cognitive self-reinforcement were obtained in the seventh and 10th grades from students participating in two independent drug prevention trials (control group participants only, N = 3, 939). Assessment of alcohol use was obtained when participants were young adults (23–26). A model distinguishing four subtypes of self-management skills fit best for both the seventh and 10th grades. While findings indicated modest stability in class structure over time, maintaining class membership characterized by high cognitive self-reinforcement and high affective self-regulation was consistently protective in terms of young adult alcohol use relative to movement from this to other classes. Transitions in class membership involving an expansion of self-management strategies were protective and associated with lower levels of young adult alcohol use and transitions involving a contraction of self-management strategies associated with higher young adult alcohol use. This study illustrates the important use of person-centered techniques to exemplify how typologies of self-management during adolescence can play a protective role in young adult alcohol use.